Biocultural Calendars Across Four Ethnolinguistic Communities in Southwestern South America - Rozzi Marin, Ricardo Roberto; Alvarez, Ricardo; Castro, Victoria; Nunez, David; Ojeda Villarroel, Jaime Andrés; Tauro, Alejandra; Massardo Vega, Cristina Elvira Francisca (My University, 2023)
Since the mid-20th century, the so-called Great Acceleration (sensu Steffen et al., 2007, https://doi.org/10.1579/0044-7447(2007)36[614:TAAHNO]2.0.CO;2) has amplified processes of ecosystem degradation, extinction of biological species, displacement of local peoples, losses of languages, and cultural diversity. These losses are still underperceived by the academic community, and by a global society that is disconnected from biocultural diversity. To reconnect society with biocultural diversity, we integrate temporal and spatial dimensions of seasonal cycles, by combining two conceptual frameworks: ecological calendars and the "3Hs" model of the biocultural ethic (sensu Rozzi, 2012, https://doi.org/10.5840/enviroethics20123414). The latter values the vital links between human and other-than-human co-inhabitants, their life habits (e.g., cultural practices of humans or life cycles of other-than-human species), and the structure and processes of their shared habitats. This integration enhances an understanding of links between cultural practices and the life cycles of biocultural keystone species. As a synthesis, we use the term biocultural calendars to emphasize their co-constitutive nature that result from interactions between dynamic biophysical and cultural processes embedded in specific ecosystems and cultures. These calendars link astronomical, biological, and cultural seasonal cycles that sustain life and enhance the integration of Indigenous and scientific knowledge to confront challenges of climate change faced from local to global scales. To illustrate this integration, we examine cultural practices and socio-environmental changes across four contrasting ethnolinguistic communities in southwestern South America, from southern to northern Chile along a marked climatic gradient to show the broad application of the concept of biocultural calendars. Plain Language Summary We combine ecological calendars and the biocultural ethic. The first refers to natural or seasonal calendars and focuses on the temporal scale of life cycles and other ecological phenomena observed at a given place. The second emphasizes the vital links among human and non-human co-inhabitants, their habits (e.g., cultural practices of humans or life cycles of other-than-human species) in shared habitats (the "3Hs" of the biocultural ethic). Close observation of biological and cultural diversity, and their interrelationships (in short, biocultural diversity), synchronizes cultural practices with natural processes at specific places. This synchrony is particularly relevant in the context of climate change because by being locally attuned, communities enhance their capacity to adapt their activities to the variability of temperature, rainfall, and other climatic events. In this article we use the term biocultural calendars to more closely understand the links between different life habits in contrasting habitats and annual seasons. In this way, biocultural calendars provide an understanding of biological and cultural heterogeneity in different seasons and regions of the world that can help us adapt to a rapidly changing world.
Keywords: biocultural ethics; chile; climate change; conservation; ecology; worldviews